Two ways to look at learning regions in the context of globalization: The homogenizing and particularizing approaches - Crevoisier, Olivier (My University, 1999)
Despite the countless publications on the subject, globalization remains a black box. On the descriptive level, there is relative consensus as to the facts, but the meaning is not truly understood. As a result, extremely contradictory hypotheses circulate, ranging from the ’end of geography' the global village and the borderless ’global company' to those who highlight the development of territorialized forms of production and the role of proximity. This article brings out the different ways of viewing this phenomenon and their consequences. The main rift between the different approaches is between ’homogenizing' approaches and ‘particularizing' approaches. The former postulate that any phenomenon may be viewed within a ’universal' scheme that is ‘a priori' deemed sufficient to explain reality, while the latter are based on the irreducible singularity of each case and propose constantly evolving explanatory schemas.
Keywords: flexible specialization; epistemology; globalization; innovative milieu; learning region